Heritability of clubfoot: A twin study. (February 2014) - Engell, Vilhelm; Nielsen, Jan; Damborg, Frank; Kyvik, Kirsten Ohm; Thomsen, Karsten; Pedersen, Niels Wisbech; Andersen, Mikkel; Overgaard, Søren
Introduction: The aetiology of congenital clubfoot is unclear. Although studies on populations, families, and twins suggest a genetic component to the aetiology, other studies have identified environmental factors. The purpose of this study was to calculate heritability in order to determine to what extent genetic and/or environmental factors contribute to the aetiology of congenital clubfoot and to asses whether there was a change in the prevalence over time. Materials and Methods: The Odense based Danish Twin Registry is unique as it contains data on all the approximately 85, 000 twin pairs born in Denmark over the last 140 years. All 46, 418 twin individuals born from 1931 through 1982, who had earlier consented to contact, received a 17-page Omnibus questionnaire in the spring of 2002. Data were analysed with structural equation models to identify the best fitting aetiological model based on a balance of goodness-of-fit and parsimony and to estimate heritability. Results: We found an overall self-reported prevalence of congenital clubfoot of 0.0027 (95 % confidence interval 0.0022–0.0034). Fifty-five complete (both twins answered the question) twin pairs were identified representing 12 monozygotic, 22 same-sex dizygotic, 18 opposite-sex dizygotic, and 3 with unclassified zygosity. The model with only environmental factors (CE) was best fitting based on AIC, and the model with an additive genetic factor (ACE) came in second. Due to the small statistical power, we hypothesise that the model with both genetic and environmental effects (ACE) was the better model. Choosing the ACE-model we found a heritability of clubfoot of 30 %. Regression coefficient for age was −0.002 (−0.011 to 0.005), indicating that there has been no change in prevalence of clubfoot over the 50-year age span we examined. Discussion: We conclude that non-genetic factors must play a role, and a genetic factor might contribute, in the aetiology of congenital clubfoot.